Alterations In Gut Microbiota Composition And Their Association With Relapse Risk In Relapsing-Remitting Multiple Sclerosis: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Relapsing-remitting multiple sclerosis (RRMS) is a chronic autoimmune neurological disease characterized by episodic relapses and progressive disability. Emerging evidence suggests that gut microbiota dysbiosis influences immune responses, neuroinflammation, and disease activity in RRMS.Objective: This systematic review aimed to synthesize current evidence on gut microbiota alterations associated with relapse risk in RRMS patients and to evaluate the therapeutic potential of microbiota-targeted interventions.Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, Embase, and Google Scholar for studies published between 2010 and 2025. Observational studies, randomized controlled trials (RCTs), and dietary or probiotic interventions examining gut microbiota composition, diversity, or modulation in RRMS were included. Data extraction focused on microbial taxa, diversity indices, clinical outcomes, and immunological markers. Narrative synthesis was employed due to heterogeneity in study design and outcomes.Results: Eleven studies were included, encompassing cross-sectional, cohort, and interventional designs. RRMS patients exhibited consistent depletion of SCFA-producing taxa (e.g., Roseburia, Faecalibacterium, Lachnospiraceae) and enrichment of pro-inflammatory taxa (Bilophila, Desulfovibrio, Bact2 enterotype). Dysbiosis correlated with higher relapse risk, disability progression, and inflammatory cytokine profiles. Probiotic supplementation, ketogenic, plant-based, and high-vegetable/low-protein diets partially restored microbial diversity, increased neurotrophic factors (BDNF), and reduced fatigue and relapse frequency.Conclusion: Gut microbiota alterations represent both a mechanistic contributor to RRMS relapse risk and a promising target for intervention. Integrating microbiome-based biomarkers with clinical management may facilitate early detection, personalized therapies, and relapse reduction in RRMS.